Effect of BRCA germline mutations on breast cancer prognosis: A systematic review and meta-analysis. Issue 40 (October 2016) - Baretta, Zora; Mocellin, Simone; Goldin, Elena; Olopade, Olufunmilayo I.; Huo, Dezheng
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The contribution of BRCA germline mutational status to breast cancer patients' prognosis is unclear. We aimed to systematically review and perform meta-analysis of the available evidence of effects of BRCA germline mutations on multiple survival outcomes of breast cancer patients as a whole and in specific subgroups of interest, including those with triple negative breast cancer, those with Ashkenazi Jewish ancestry, and patients with stage I–III disease. Methods: Sixty studies met all inclusion criteria and were considered for this meta-analysis. These studies involved 105, 220 breast cancer patients, whose 3588 (3.4%) were BRCA mutations carriers. The associations between BRCA genes mutational status and overall survival (OS), breast cancer-specific survival (BCSS), recurrence-free survival (RFS), and distant metastasis-free survival (DMFS) were evaluated using random-effect models. Results: BRCA1 mutation carriers have worse OS than BRCA -negative/sporadic cases (hazard ratio, HR 1.30, 95% CI: 1.11–1.52) and worse BCSS than sporadic/ BRCA -negative cases among patients with stage I–III breast cancer (HR 1.45, 95% CI: 1.01–2.07). BRCA2 mutation carriers have worse BCSS than sporadic/ BRCA -negative cases (HR 1.29, 95% CI: 1.03–1.62), although they have similar OS. Among triple negative breast cancer, BRCA1/2 mutations carriers had better OS than BRCA -negative counterpart (HR 0.49, 95% CI: 0.26–0.92). Among Ashkenazi Jewish women, BRCA1/2 mutations carriers presented higher risk of death from breast cancer (HR 1.44, 95% CI: 1.05–1.97) and of distant metastases (HR 1.82, 95% CI: 1.05–3.16) than sporadic/ BRCA -negative patients. Conclusion: Our results support the evaluation of BRCA mutational status in patients with high risk of harboring BRCA germline mutations to better define the prognosis of breast cancer in these patients.